Surface strategies for catalytic CO2 reduction: from two-dimensional materials to nanoclusters to single atoms. (7th October 2019) - Wang, Liming; Chen, Wenlong; Zhang, Doudou; Du, Yaping; Amal, Rose; Qiao, Shizhang; Wu, Jianbo; Yin, Zongyou
Abstract : This work constructively reviewed and predicted the surface strategies for catalytic CO2 reduction with 2D material, nanocluster and single-atom catalysts Abstract : Redox catalysis, including photocatalysis and (photo)electrocatalysis, may alleviate global warming and energy crises by removing excess CO2 from the atmosphere and converting it to value-added resources. Nano-to-atomic two-dimensional (2D) materials, clusters and single atoms are superior catalysts because of their engineerable ultrathin/small dimensions and large surface areas and have attracted worldwide research interest. Given the current gap between research and applications in CO2 reduction, our review systematically and constructively discusses nano-to-atomic surface strategies for catalysts reported to date. This work is expected to drive and benefit future research to rationally design surface strategies with multi-parameter synergistic impacts on the selectivity, activity and stability of next-generation CO2 reduction catalysts, thus opening new avenues for sustainable solutions to climate change, energy and environmental issues, and the potential industrial economy.